Cut and paste: The first uses of collage and photomontage in the representation of modern architecture - Linares García, Fernando (Estoa. Journal of the Faculty of Architecture and Urbanism, 2018)
The graphic techniques of collage and photomontage, born within avant-garde art of the 1920s, mainly in Cubism, spread through and permeated all other arts, including architecture. Based on cutting and pasting elements or remnants of diverse materials in new combinations to express novel artistic principles and meanings, these apparently simple techniques offered strong potential for design and conceptualisation. They were widely used by some of the most important figures in Russian Constructivism, the Bauhaus and the Modern Movement, such as Frank Lloyd Wright, Le Corbusier and Mies van der Rohe.